Criminal proceedings, justice and social rehabilitation: a vision of the Ecuadorian reality (Revista revoluciones, 2024)
Objective: identify the main elements that comprise criminal justice processes and conduct an analysis of the country’s social rehabilitation system. Method: a review methodology was applied, using the PRISMA method as a structural basis. The following databases were utilized: SCIELO, Google Scholar, EBSCO, Education Resources Information Center (ERIC), PsycINFO, Psycnet, and Dialnet. The search criteria were based on the keywords “justice,” “criminal sanction processes,” and “social rehabilitation.” Results: the elements that comprise criminal processes include instruction, preparation, and trial. Regarding Ecuador’s judicial system, it is structured as a system of legal pluralism, grounded in military and indigenous justice and featuring an intercultural perspective. Conclusions: there is significant corruption within Ecuadorian justice that has persisted for years, reflecting the same reality across Latin America. Regarding prisons, there is no true rehabilitation and social reintegration process; rather, Ecuadorian prisons are characterized by the deterioration of their system.
Keywords: justice; criminal sanction processes; social rehabilitation